2002
DOI: 10.1002/int.10052
|View full text |Cite
|
Sign up to set email alerts
|

Comparing a genetic fuzzy and a neurofuzzy classifier for credit scoring

Abstract: In this paper, we evaluate and contrast two types of fuzzy classifiers for credit scoring. The first classifier uses evolutionary optimization and boosting for learning fuzzy classification rules. The second classifier is a fuzzy neural network that employs a fuzzy variant of the classic backpropagation learning algorithm. The experiments are carried out on a real life credit scoring data set. It is shown that, for the case at hand, the boosted genetic fuzzy classifier performs better than both the neurofuzzy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Hoffmann et al [5] used ACO to predict credit rating of customers in various datasets and their results show that ACO produces the rules that yield 71.9% prediction accuracy. Parpinelli et al [19] proposed the ACO-based data miner for inducting rules from data.…”
Section: Related Workmentioning
confidence: 99%
“…Hoffmann et al [5] used ACO to predict credit rating of customers in various datasets and their results show that ACO produces the rules that yield 71.9% prediction accuracy. Parpinelli et al [19] proposed the ACO-based data miner for inducting rules from data.…”
Section: Related Workmentioning
confidence: 99%
“…It has been found that in most cases the ensembles produce more accurate predictions than the base classifiers (Dietterich, 1997). Hoffmann, Baesens, Martens, Put, and Vanthienen, 2002) reported that the boosted genetic fuzzy classifier performed better than both the neuro fuzzy classifier and C4.5 algorithm. (West et al, 2005) reported that ensemble model of NNs obtained the higher accuracy than the single NN in credit risk evaluation and bankruptcy prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that aggregating approach can easily achieve improved accuracies by an aggregation of individual classifiers for credit scoring as well as the classification application. (Hoffmann et al, 2002) reported that the boosted genetic fuzzy classifier performed better than both the neuro fuzzy classifier and C4.5 algorithm. (West (2005)) reported that ensemble model of NNs obtained the higher accuracy than the single NN in credit scoring and bankruptcy prediction.…”
Section: Introductionmentioning
confidence: 99%